Kinetics and Thermodynamics of Grape Cake Drying (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
In this work, several different drying methods were used to organize deep processing of grape residues collected at grape processing plants using waste-free technology. The initial moisture content of grape cake is 49,36 ± 3,45%. Grape cake composition is considered a good raw material for the production of biofuel products of the second generation. During the experiment, the drying efficiency of a vacuum dryer, conventional drying and drying in the open sun were studied.